Emerging Trends in Oral Health Sciences and Dentistry - Singh Virdi, Mandeep (IntechOpen, 2015)
Emerging Trends in Oral Health Sciences and Dentistry is the second book on Oral Health Science. The first book is Oral Health Care-Pediatric, Research, Epidemology and clinical Practices and Oral Health Care-Prosthodontics, Periodontology, Biology, Research and systemic Conditions published in February 2012. The present book is a reflection of the progress in Oral Health Sciences, practices and dentistry indicating the direction in which this stream of knowledge and education is likely to head forward. The book covers areas of General Dentistry, Paediatric and Preventive Dentistry, Geriatric and Prosthodontics, Orthodontics, Periodontology, Conservative Dentistry and Radiology and Oral Medicine.